Turnover of 131I-Fibrinogen in Mercury Chloride Intoxicated Dogs - Gałasinski, W; Worowski, K; Niewiarowski, S; Franecki, G (Thrombosis and Haemostasis, 1967)
The turnover of 131I-fibrinogen, studied in 15 normal dogs, amounted on the average to 2.6 days. The fibrinogen level considerably increased but the biological half-life time of 131I-fibrinogen was significantly shorter in mercury chloride intoxicated dogs, particularly in the first phase of intoxication.It has been concluded that the fibrinolytic enzymes connected with kidney and depleted in intoxicated dogs are not essential for the fibrinogen catabolism. The elevation of fibrinogen in mercury chloride intoxication is not directly caused by the inhibition of fibrinolytic enzymes.Possible explanations of the accelerated turnover of fibrinogen in HgCl2 treated dogs were discussed.